Redescription of Steleocoris Mayr, 1864 and Theloris Thunberg, 1783 (Hemiptera: Pentatomidae), two poorly known African stink bugs - Da Silva, Jaqueline Santana Tavares Ferreira; Grazia, Jocelia; Barão, Kim Ribeiro (Zootaxa, 2021)
The knowledge about the monotypic genera Steleocoris Mayr and Theloris Thunberg is restricted to their original descriptions and subsequent nomenclatural acts. These genera are primarily distributed in South Africa and are two of the few genera of Carpocorini (Pentatomidae: Pentatominae) occurring in Africa. Here, we redescribe Steleocoris comma (Thunberg) and Theloris costata (Thunberg) and illustrate the genitalia of both sexes for the first time. Also, an occurrence map is provided based on collection labels from analyzed specimens and records available on GBIF and the web repository iNaturalist.org.